The Implementation of Giving Task Method to Improve Students’ Achievement - Yopi Nisa Febianti (STKIP Singkawang, 2020)
There are some learning methods used by educators that aim to motivate learners to be diligent and enjoy learning. Learners who have high motivation to learn will play an active role, critical thinking, social interaction, creativity, and focus while learning. One of the methods that can encourage the creativity of learners in learning to improve creativity and knowledge for achieving satisfying learning outcomes is the assignment method. This research aims to analyze whether or not the giving-task method can improve students’ achievement in the letter of credit material. The method used in this research is class action research that consists of two cycles, starting from planning, giving treatment, and reflection. To collect the data, the writer uses a subjective test. The data source is the first-grade students (I.B) of the Economic Education Department Faculty of Teachers’ Training And Educational Sciences UGJ. The result of this research shows that giving task method can improve students’ achievement. It is shown from the satisfying score got by students. In the first cycle, the average score is 45.29 while in the second cycle, it is 89.00. This research concludes that the giving-task method can help students comprehending the letter of credit concept and it develops the students’ responsibilities individually or in group work and their creativities during the learning process.